Pakistan : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2010)
The distribution of poor population in Pakistan suggests that almost 75 percent of the poor are clustered around the poverty line. The economy moved to a higher growth trajectory in the vicinity of 6-7 percent real GDP growth during FY 2002-07, and resultantly the poverty declined substantially in FY 2004/05. The productive capacity of the economy remained alien to this higher growth and new industrial capacity was hardly added to the economy. The fiscal year 2007/08 was a volatile year for Pakistan's economy both on domestic and external fronts.